Удосконалення трифазного перетворювача для комбінованих систем електроживлення локальних об’єктів з фотоелектричною сонячною батареєю - Шавьолкін, Олександр Олексійович (НТУ "ХПІ", 2018)
Розглянуто принципи формування струму багатофункціонального трифазного перетворювача для комбінованих систем електроживлення локальних об’єктів з фотоелектричною сонячною батареєю та підтриманням близького до одиниці коефіцієнту потужності у точці підключення до мережі за цілодобового використання. Запропоновано використання комбінованої модуляції з релейним регулятором струму, що дозволяє забезпечити відповідні стандартам показники струму мережі із найменшими втратами енергії в ключах. Розроблено структуру керування, що забезпечує реалізацію. Моделювання в системі "мережа-перетворювач-нелінійне навантаження" з оцінкою втрат потужності в ключах за різних принципів формування струму підтверджує ефективність запропонованих рішень.

The purpose of the work is to improve the principles of forming the output current of a grid inverter to ensure compliance with the standards of parameters of a grid current without increasing the energy losses in the inverter's keys. The application is considered in a multifunctional three-phase converter with round-the-clock use for combined power supply systems of local objects, which provides a power factor close to unity at the point of connection to the AC grid. The methods of the electric circuit theory were used in combination with computer simulation. The analysis of the known principles of forming of an instantaneous value of output current of inverter by the deviation from the referenced value at a constant and variable key switching frequency is performed. For a grid three-level inverter, the use of combined unipolar and bipolar modulation with a relay current controller is suggested. The structure of the current controller is designed to provide the distribution of the unipolar and bipolar modulation intervals in accordance with the referenced value of inverter current and the mains voltage. A mathematical model is developed for studying the processes in the system, which include "a grid - the converter - non-linear unbalanced load", with an estimate of the power losses in the keys of a grid inverter in accordance with their currents and data sheets used, for a different principles of current formation for a two-level and three-level bridge a grid inverter. The results of the simulation confirm the possibility of ensuring the harmonic composition of the grid current corresponding to the standards with the lowest energy losses in the keys in all modes of the converter operation when using a three-level NPC inverter with clamped diodes. Further improvement in performance is possible when using the structure of three-level TNPC inverters.
Improvement of a three-phase converter for combined power supply systems for local objects with a photovoltaic solar battery
Keywords: трирівневий інвертор; силовий активний фільтр; релейний регулятор струму; відхилення струму; коефіцієнт гармонік; коефіцієнт потужності; втрати потужності; power active filter; relay current controller; current deviation